Nonlinear dalembert equation in the pseudo-euclidean space r2,n and its solutions - Yuryk, Ivan (Springer Science, Ukr.Math.J., 2000)
We investigate the nonlinear Dalembert equation in thepsevdo-euclidean space R2,n and construct nev exact solutions containing arbitrary functions. Досліджено нелінійне рівняння Даламбера в псевдо-евклідовому просторі R2,n і побудовано нові точні розвязки,які містять довільні функції.
Keywords: Dalambert equations; pseudo-euclidean space; exact solutions; рівняння Даламбера; псевдо-евклідовий простір; точні розвязки; кафедра вищої математики імені проф. Можара В. І.